2020
DOI: 10.1186/s12929-020-0617-7
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane protein A (OmpA) as a potential therapeutic target for Acinetobacter baumannii infection

Abstract: Acinetobacter baumannii (A. baumannii) is an important opportunistic pathogen causing serious nosocomial infections, which is considered as the most threatening Gram-negative bacteria (GNB). Outer membrane protein A (OmpA), a major component of outer membrane proteins (OMPs) in GNB, is a key virulence factor which mediates bacterial biofilm formation, eukaryotic cell infection, antibiotic resistance and immunomodulation. The characteristics of OmpA in Escherichia coli (E. coli) have been extensively studied si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(152 citation statements)
references
References 91 publications
0
126
0
3
Order By: Relevance
“…SuOMV, sOMV, and nOMV had different zeta potential, which may also be associated with their potency to induce different levels of immune response. OmpA was found to be a predominant virulence factor which plays key roles in regulating the adhesion, aggressiveness, and biofilm formation of A. baumannii (61,62). The highest level of OmpA-specific IgG was observed in mice vaccinated with SuOMV, though the highest percentage of OmpA was included in sOMV.…”
Section: Discussionmentioning
confidence: 99%
“…SuOMV, sOMV, and nOMV had different zeta potential, which may also be associated with their potency to induce different levels of immune response. OmpA was found to be a predominant virulence factor which plays key roles in regulating the adhesion, aggressiveness, and biofilm formation of A. baumannii (61,62). The highest level of OmpA-specific IgG was observed in mice vaccinated with SuOMV, though the highest percentage of OmpA was included in sOMV.…”
Section: Discussionmentioning
confidence: 99%
“…Outer membrane proteins play an important role in the survival, drug resistance, and pathogenicity of A. baumannii [ 22 ]. Deletion or mutation of key outer membrane proteins can seriously affect the survival and pathogenicity of A. baumannii [ 23 ]. Okada et al [ 17 ] confirmed that the MacA-MacB-TolC tripartite complex is a transmembrane machine and can actively extrude substrates, including macrolide antibiotics, virulence factors, peptides, and cell envelope precursors.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that this approach reduces the bacteria’s ability to evade the host’s immune system, allowing more time to clear the infection [ 96 ]. Nie et al have written a timely review discussing non-antibiotic options for OmpA inhibition of MDR infections [ 97 ].…”
Section: Porinsmentioning
confidence: 99%